Naples prognostic score as a novel prognostic prediction indicator in adult asthma patients: A population-based study - Ning Zhu, MD; Shanhong Lin, MD; Hang Yu, MD; Fang Liu, MD; Weina Huang, MD; Chao Cao, PhD (World Allergy Organization Journal, 2023)
Objective: This study was to evaluate the prognostic value of the Naples prognostic score (NPS) in adult patients with asthma. Methods: Data on 44 601 participants from the 1999–2018 National Health and Nutrition Examination Survey (NHANES) were analyzed. The NPS was calculated based on serum albumin, total cholesterol, neutrophil-to-lymphocyte ratio (NLR), and lymphocyte-to-monocyte ratio (LMR), and participants were divided into 3 groups. Self-administered questionnaires were used to collect information on asthma, and mortality was identified using the National Death Index through December 31, 2019. Multiple logistic regressions were used to analyze the relationship between NPS and its components and the prevalence of asthma. Kaplan-Meier survival analysis, Cox proportional regressions, and the random survival forest (RSF) were used to assess the significance of NPS and its components in predicting all-cause and cause-specific (cardiovascular, cancer, and respiratory diseases) mortality in asthma patients. Results: The mean age of the participants was 47.59 ± 0.18 years, and 48.47% were male. The prevalence of asthma was 13.11%. The participants were categorized into 3 groups: 8306 (18.6%) participants were in group 0 (NPS 0), 30 842 (69.2%) were in group 1 (NPS 1 or 2), and 5453 (11.2%) were in group 2 (NPS 3 or 4). Compared to the reference group, participants in group 2 had a higher prevalence of asthma (odds ratio [OR] = 1.40 [1.24–1.56]). Participants with asthma in group 2 had a significantly increased risk of all-cause mortality (hazard ratio [HR] = 2.42 [1.67–3.50]), cardiovascular mortality (HR = 2.68 [1.50–4.79]), cancer mortality (HR = 2.10 [1.00–4.45]), and respiratory disease mortality (HR = 3.00 [1.18–7.65]) compared to those with asthma in group 0. The RSF showed that NPS had the highest value in predicting all-cause mortality in adults with asthma, compared to its components. Conclusions: The results of this study indicate that the NPS is a powerful prognostic indicator for outcomes in asthma patients.